AKIBAT HUKUM TERHADAP PEMERINTAH APABILA TIDAK MEWUJUDKAN KEWAJIBANNYA DALAM MEMBERIKAN JAMINAN KECELAKAAN KERJA DAN JAMINAN KEMATIAN KEPADA PEGAWAI APARATUR SIPIL NEGARA (ASN) - Muhammad Ali Adnan (Jurnal Hukum Kaidah: Media Komunikasi dan Informasi Hukum dan Masyarakat, 2021)
The social security program is one of the programs that is considered strategic in realizing the welfare of the people in many countries. By reason of the purpose of establishing a country is to achieve prosperity (welfare state) which is the government's commitment as its responsibility as the manager of the state. Social welfare development in Indonesia actually refers to the concept of a welfare state. Social security is also the right of State Civil Apparatus Employees (ASN). What is meant by the State Civil Apparatus Employees are the civil servants and the government employees with work agreements who are appointed by a civil servant development official and assigned tasks in a government position or entrusted with other state duties and are paid based on statutory regulations.Based on the background described above, this research will discuss 3 (three) problems, namely how are the government's obligations in the health services, how is the Work Accident Insurance and Death Benefit for the State Civil Apparatus (ASN) and what are the legal consequences for the government if it does not fulfill its obligations in providing the Work Accident Insurance and Death Benefit for the State Civil Apparatus ( ASN).To fulfill the order of the Constitution of 1945 and the Article 92 of the Law Number 5 of 2014 concerning the State Civil Apparatus, the Government issued Government Regulation Number 70 of 2015 concerning the Work Accident Insurance and Death Benefit for the State Civil Apparatus Employees. The Government Regulation explains that the Work Accident Insurance is the protection against the risk of the work accidents or the occupational diseases in the form of treatment, compensation, and disability benefits. Then, Death Benefit is the protection against the risk of death not due to a work accident in the form of death benefit. The Work Accident Insurance and Death Benefit Program include the participation, benefits and contributions. Based on this, the government has an obligation to provide protection for the work accident insurance and death benefit as regulated in the Law Number 5 of 2014 concerning the State Civil Apparatus. Government actions that are negligent or intentionally do not carry out their obligations in protecting work accident insurance and death benefit certainly have legal consequences and are human rights. For this action, legal action can be taken in the form of a group representative lawsuit. It is done by following the procedure as regulated in the Regulation of the Supreme Court Number 1 of 2002 concerning the Lawsuit Procedure for Group Representatives. Furthermore, against the government's actions, every citizen can also take legal action against citizens (Citizen Lawsuit).